Advantage of liver stiffness measurement before and after direct‐acting antiviral therapy to predict hepatocellular carcinoma and exacerbation of esophageal varices in chronic hepatitis C. Issue 4 (12th January 2020) - Ogasawara, Nobuhiko; Saitoh, Satoshi; Akuta, Norio; Sezaki, Hitomi; Suzuki, Fumitaka; Fujiyama, Shunichiro; Kawamura, Yusuke; Hosaka, Tetsuya; Kobayashi, Masahiro; Suzuki, Yoshiyuki; Arase, Yasuji; Ikeda, Kenji; et al.
Abstract : Aim: The risk of development of hepatocellular carcinoma (HCC) persisted in patients with advanced fibrosis, even after achieving sustained virologic response (SVR). This study aimed to show the advantage of liver stiffness measurement (LSM) at baseline and after SVR to predict HCC occurrence and esophageal varices (EV) exacerbation. Methods: These risks were evaluated in 398 chronic hepatitis C patients without a history of HCC who achieved SVR after direct‐acting antiviral agent and evaluated LSM at least twice during follow up. We defined liver cirrhosis and chronic hepatitis as LSM of ≥12 kPa and <12 kPa, respectively. Results: LSM was significantly correlated with serum fibrosis markers, such as Fib‐4 index and Wisteria floribunda agglutinin‐positive Mac‐2 binding protein, at baseline and SVR at 24 weeks after treatment (SVR24). Five patients received preventive treatment of EV, but no EV bleeding occurred after SVR, and their LSM at baseline and SVR24 was significantly higher than that of other cirrhosis patients. The annual rate of HCC during the first 4 years was 1.5%. LSM in HCC patients tended to decrease after direct‐acting antiviral agent therapies, but significantly higher than that of cirrhosis patients without HCC before and after treatment. Multivariate analysis identified LSM and alpha‐fetoprotein at baseline and LSM at SVR24 as significant independent predictors of HCC. Conclusions: Evaluating LSM not only at baseline, but also SVR24, was found to be useful for the detection of advanced fibrosis patients at high risk of HCC occurrence and EV exacerbation. We recommend focused surveillance of HCC and EV for these patients.